REDESIGN UI/UX WEBSITE OPEN LIBRARY TELKOM UNIVERSITY BERDASARKAN TIPE KEPRIBADIAN INFLUENCE DENGAN METODE DESIGN THINKING - Puspitaningrum, Dian Novitasari; Perdana, Ilham; Utama, Nur Ichsan (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
This study applies a design thinking methodology approach to redesign the user interface and user experience on the Telkom University Open Library website by considering the type of influence on personality. The influential personality type discussed in this study is the DISC model which describes individuals as friendly, warm, and highly socially skilled. The main goal of this redesign is to provide a comfortable and satisfying experience for Telkom University students, who have influential personality types when interacting with the Open Library website service. The design thinking method is applied through six main steps, which are; empathize, define, imagine, prototype, test and execute. Testing of proposed changes is done using two methods, namely usability testing and user acceptance testing (UAT). Research results show that by taking into account the influencer's personality type and applying Gestalt principles and material design as design guides, the redesign successfully achieved the goal of meeting needs and increasing satisfaction of users with influencer personality types when using Telkom Open University. Library website. Therefore, applying a design thinking approach in redesigning the user interface and user experience on the Telkom University Open Library website, taking into account the influencer's personality type and following the principles of Gestalt and Material Design, successfully achieved the goal of increasing user satisfaction. with an influential personality type. visit website.